2003
DOI: 10.1021/ja034705n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evidence for a Tetrameric Transition State in the Asymmetric Autocatalytic Alkylation of Pyrimidyl Aldehydes

Abstract: Experimental kinetic data coupled with kinetic modeling implicates a tetrameric transition state in the Soai autocatalytic alkylation of pyrimidyl aldehydes. The kinetic model accurately predicts both the reaction rate and the amplification in enantiomeric excess observed in reactions carried out under a wide range of conditions. These studies reveal the Soai reaction to be an example of true autocatalytic efficiency in a template-directed "minimal system" for self-replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 14 publications
0
82
0
3
Order By: Relevance
“…A variation in only one of the fitted parameters in the monomeric mechanism (model 2) leads to a qualitative reproduction of the kinetic results of Blackmond et al (20). Hence arguments that have been previously promoted to exclude monomer catalysis (18,20,22,23) have to be reassessed. In fact, our simulations give slight indication for a monomeric instead of a dimeric catalytic pathway because of the better agreement of model 2 with the experimental kinetic data reported by Gridnev et al (16).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…A variation in only one of the fitted parameters in the monomeric mechanism (model 2) leads to a qualitative reproduction of the kinetic results of Blackmond et al (20). Hence arguments that have been previously promoted to exclude monomer catalysis (18,20,22,23) have to be reassessed. In fact, our simulations give slight indication for a monomeric instead of a dimeric catalytic pathway because of the better agreement of model 2 with the experimental kinetic data reported by Gridnev et al (16).…”
Section: Resultsmentioning
confidence: 80%
“…Blackmond and coworkers (20) conducted a series of calorimetrically monitored kinetic studies from which it was first concluded that the catalyst is dimeric, and then later that it is tetrameric (23) or even multimeric. In these experiments no mirror-symmetry breaking has been mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] We developed a modified Kagan ML 2 model 10,13,14 (Scheme 2) for autocatalytic asymmetric amplification in the case of substrate 1 with R=CH 3 , where the reaction product 2' forms dimers 10 (or tetramers 11,[15][16][17][18] ) that serve as the active autocatalytic species. Our work demonstrated that dimers are formed stochastically, with equal probability of forming homo-(D RR and D SS ) and heterochiral (D RS ) species (K dimer = 4).…”
Section: Scheme 1 Soai Autocatalytic Reaction Initiated By An Isotopmentioning
confidence: 99%
“…Certain chemical reactions are indeed known to have such properties (Soai et al, 1995, Sato et al 2003, Mathew et al, 2004. It is important to point out that these reactions are only based on dimerization, but they are nevertheless quite valuable in establishing the basic elements of homochiralization in chemical systems (Kitamura et al 1998, Plasson et al 2004, and can lead to quantitative predictions (Blackmond et al 2001, Buono andBlackmond 2003). For a recent review see the paper by Mislow (2003).…”
Section: Introductionmentioning
confidence: 99%